(untitled) (Biological Sciences - PJSIR, 2009)
The effect of age at mating of male and female warehouse moth, Ephestia cautella (Walker), soon after the emergence or delayed for 1-5 days was studied on the number of eggs laid (fecundity), egg viability, longevity and adult emergence. It was found that with the delay in mating after emergence of male, female or both, the number of eggs laid decreased proportionately. Egg viability decreased when female or both male and female were delayed from mating for more than 4 days. Male insects, that were delayed from mating, lived longer than the females delayed from mating. Average male and female longevity in all the treatments was 10 and 7 days, respectively. Delayed mating had significant effect on females than on males. Unmated males lived longer than the mated males. Thus methods that can delay and disrupt mating may be effective behavioural strategies for managing E. cautella.